FlowSpy: exploring Activity-Execution Patterns from Business Processes - Tristão, Cristian; Ruiz, Duncan D.; Becker, Karin (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2008: Anais do IV Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2008.5923, 2008)
The paper describes FlowSpy, an environment that employs a sequence mining technique to discover and analyze actual process execution paths from business processes, for both process comparison and process discovery. FlowSpy focuses on exploratory analysis of the different execution flows, enabling a detailed analysis of business behavior, quantification of different execution flows, and abstraction mechanisms (log pre-processing and visualization abstraction) that deal with process complexity and different process views. Log pre-processing aims at improving the data mining phase, with a more restricted aggregate tree. Visualization abstraction facilitates pattern interpretation by producing trees that represent the obtained patterns.